Structural studies of cell adhesion and division - Yates, LA (2012)
Cell adhesion is a critical process that allows the organisation and functioning of tissues in three-dimensions. However, the replenishing of cells, via cell division, within tissues is equally important for functioning complex life. Both cell adhesion and division are tightly controlled processes and rely on a complex network of signals that, as yet, are not wholly understood. This Thesis presents a structural analysis of several proteins involved in these processes. In the case of cell adhesion, we have made use of high-throughput (HTP) cloning and expression screening technologies in the Oxford Protein Production Facility (OPPF) for the study of the Kindlin protein family – a recently discovered set of proteins essential for integrin-mediated cell adhesion. As a direct result of the HTP pipeline used we were able to determine the high resolution crystal structure of a single domain, the Pleckstrin Homology Domain, from the isoform Kindlin-1. Deletion of this domain in the full-length protein resulted in impaired integrin activation in vivo. This structure, in combination with molecular dynamics simulation demonstrated that, unlike other well characterised PH domains, the binding of secondary messenger lipids (phosphoinositides) is dictated by a, previously unseen, salt bridge that occludes the putative binding site. Mutation of the salt bridge alters the binding characteristics of this domain in vitro. In addition to the PH domain, we have also studied and biophysically characterised full-length Kindlin-3, a blood cell specific isoform. By optimising baculovirus-infected Sf9 cell expression systems we were able to obtain, for the first time, sufficient quantities of protein for characterisation. Furthermore, by using small-angle X-ray scattering (SAXS) in solution we were able to determine a low resolution solution structure of Kindlin-3, revealing a linear arrangement of its FERM domain - a novel conformation known only otherwise in talin. We characterised the interaction of full-length Kindlin-3 with β-integrin cytoplasmic tails using nuclear magnetic resonance spectroscopy, which confirmed that a direct interaction with a membrane distal NPxY motif occurs, and demonstrated the importance of a preceding Serine/Threonine rich region in peptide binding. In the case of cell division, we have determined the crystal structure of the cell cycle checkpoint control related protein, Cid1, a terminal uridine tranferase from Schizzosaccharomyces pombe, alone and in complex with UTP. Structural and biochemical analysis of Cid1 identified a novel Uridine selection mechanism that is suggested to be conserved in metazoan ZCCHC enzymes involved in let-7 miRNA biogenesis, which are important for proliferation, differentiation and cell fate. We have also demonstrated that Cid1 is an RNA binding protein, a property essential for activity that employs a novel mechanism of RNA binding in the absence of RNA binding motifs. The structural work undertaken in this thesis has focussed on two distinct, but interwoven, aspects of cell biology and has significantly added to both fields of research. Excitingly, this has opened many new avenues of investigation and, in the case of Cid1, has the strong potential to lead to the development of novel anticancer therapies.